Mechanisms and Prevention Strategies of Macrophage Involvement in the Progression From Hypertension to Heart Failure - Ningning Zhang; Pengyu Cao; Bojian Wang; Jinting Yang; Lijing Zhao; Wangshu Shao (International Journal of Hypertension)
Hypertensive heart disease, a condition affecting millions worldwide, encompasses a spectrum from uncontrolled hypertension to heart failure. Despite the intricacies of its pathogenic mechanisms, recent attention has been directed toward the role of macrophages in the progression from hypertension to heart failure. Under normal circumstances, macrophages contribute to tissue homeostasis by clearing deceased cells. However, dysregulation during hypertension triggers inflammatory pathways, leading to tissue damage. Oxidative stress and mitochondrial dysfunction are implicated in this process. Exercise training, gaining popularity for its potential in regulating macrophage function, emerges as a promising intervention to improve outcomes in hypertensive heart disease. This review provides a succinct overview of previous research elucidating the involvement of macrophages in the transition from hypertension to heart failure. It underscores the current active areas of investigation and emphasizes the potential of exercise training in mediating macrophage responses, offering a glimpse into a hopeful avenue for therapeutic intervention in this challenging medical condition.